Quantization effects for a variant of the Ginzburg-Landau type system - Li Ma (Electronic Journal of Differential Equations, 2008)
The author uses Pohoaev's identity to research the quantization for a Ginzburg-Landau type functional. Under the logarithmic growth condition which is different assumption from that of in [2], the author obtain the analogous quantization results.